PENERAPAN QANUN NOMOR 11 TAHUN 2002 TENTANG AQIDAH, IBADAH DAN SYI’AR ISLAM DI KABUPATEN ACEH BARAT TAHUN 2013-2016 - Ramanda, Rozi; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Implementation of Qanun Number 11 Year 2002 on Aqidah, Worship and Islamic Shia in West Aceh district aims to maintain faith, increase understanding and practice of worship and revive and enliven activities to create atmosphere and Islamic environment, expected to be implemented by Kaffah.This research was conducted in West Aceh district. The purpose of this study is to know how the implementation of Qanun Number 11 Year 2002 and what are the obstacles faced in the implementation of Qanun Number 11 Year 2002 in West Aceh District. The benefits of this study is expected to serve as a basis for further research of the same kind. In this research use descriptive qualitative research method where data source come from Primary data and Secondary data.The results of the implementation of Qanun Number 11 Year 2002 on Aqidah, Worship and Shi'ar Islam in West Aceh District can be said to not be implemented Kaffah based on Qanun Number 11 Year 2002, this is marked by the many violations committed by the community and related parties even the violation is done repeatedly. In the implementation of Qanun Number 11 Year 2002 is expected to be reviewed about sanctions and penalties for violators who violate the Qanun.Keywords: Implementation, Qanun, Aqidah, Worship, Syi'ar Islam